(3GdMeGjI GdLfGFjI ddOe aj GdbGfhf GddjHj (B: s (3OQGSI ebGQfI (B/ s - (3RgQI GdefjQ NdjaI eGOj bGLhes; (3YeQ eMeO eMeO SGdes; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2014)
(3JYGdL GdQSGdI ETcGdjI eOi caGjI bGfhf GdYbhHGJ HbhGYOg GdJbdjOjI hGdbhGfjf GdecedI dg aj JhajQ GdMeGjI GdLfGFjI ddOe aj ehGLgI GdCaYGd GdELQGejI GdeSJMOKI GdJj JeS UMI GdEfSGf hMjGJg(B: (3MjK CUHM Oe GdEfSGf YQVI ddEUGHI HGdCeQGV GdeYOjI ceQV GdEjOR hGdhHGA GdcHOj hjUfaGf Vef GdCeQGV GdhHGFjI GdJj JMUO GdedGjjf ef GdHTQ SfhkjG(B: (3hJHQR NWhQI Jdc GdCeQGV Ydi GdOe YfO GSJNOGegG cCOGI HjO GdeLQejf dGQJcGH LQGFe eGSI HMjGI GdCaQGO hSdGeJge(B: (3aVdkG YeG jfJbd efgG Yf WQjb GdNWC Ch GdEgeGd hNGUI eG jbY ef GdCWHGA hef aj Mcege(B: (3heG jbY ef GdeDSSGJ GdYdGLjI heQGcR fbd GdOe djS Hfbd GdajQhSGJ aMSH Hd hGdOe GdeYjH YehkeG(B. (3hbO JHjf YOe hLhO MeGjI aGYdI dOe GdEfSGf MjK NdG bGfhfG GdYbhHGJ GddjHj hGdeUQj ef fU NGU jYGbH Ydi fbd ajQhS GdEjOR hZjQg ef GdajQhSGJ GdbGJdI(B: (3ceG NdG GdJTQjY Qbe (B(178) (3dSfI (B1960 (3GdNGU HJfXje fbd GdOe aj eUQ(B: (3hCjkVG GdbGfhf Qbe (B(16) (3dSfI (B1986 (3HTCf GdeSFhdjI GdWHjI ef fU NGU jYGbH GdCWHGA hef aj Mcege Ydi fbd GdOe GdeYjH HGSJKfGA eGOI hMjOI gj GdeGOI (B21 (3GdhGQOI aj GdbGfhf GdCNjQs
This paper discusses the case of adequacy of penalty law with its routine rules and other complementary laws in maintaining the blood criminal protection against created criminal offenses, that affect the human health & life. Human's blood became exposed to infectious diseases such as AIDS & Hepatitis where these two diseases are classified within epidemic diseases that cause millions of people to death annually. The potential danger of such diseases on blood when they fall into criminal hands to commit such crimes which are associated with individuals' lives and safety. Rather than what is spread as a result of mistake or negligence, especially by doctors and the like, as well as what occur by medical institutions and blood transfusion centers, not only through virus transfer but also due to defective blood in general. It is obvious that there is a lack of effective protection concerning human blood, where both Libyan & Egyptian laws of legal sanctions are free of any special statement for the punishment of transferring AIDS virus and other lethal viruses. The legislation (178) of the year 1960 associated with organizing blood transfusion in Egypt and law no. (16) of the year 1986 regarding the medical responsibility are free of any special provision which punishes doctors and the like concerning transfer of defective blood except that single article no. no. (21) included in the last law.
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdLfGFi (B2014.s
(3HHdjhLQGajG(B: (3UaMGJ (B752-791.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFj GdebGQfs; (3GdCeQGV GdeYOjI s; (3GdOe GdedhKs; (3GdajQhSGJs; (3GdJSees; (3GdbGfhf GdLfGFjs -- (3djHjGs; (3GdbGfhf GdLfGFjs -- (3aQfSGs; (3GdGYJOGA GdYeOjs; (3GdMeGjIs; (3GdOes; (3fbd GdOes; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs